Test Effectiveness Fertilizer Organic KoHeA+MF with Substance Regulator Grow Experience To Germination and Growth of Red Chili Seeds (Capsicum Annuum L.) Varieties Lotanbar - Febria Fitri; Trisia Wulantika; Yun Sondang; Wiwik Hardaningsih; Sentot Wahono (LPPM UNIVERSITAS ISLAM KUANTAN SINGINGI, 2026)
Chili Plants (Capsicum annuum L.) Red chili is one of the leading horticultural commodities, widely consumed bythe public for both culinary and medicinal purposes. The demand for red chili continues to increase alongsidepopulation growth. Consequently, increased red chili production must be accompanied by improvements inquality. The use of high-quality seeds is a major factor in enhancing both quality and yield. The planting mediumis another critical factor influencing plant growth, especially in the nursery stage. Additionally, phytohormones orplant growth regulators (PGRs) affect seed germination. This study aimed to examine the effects of differentdosages of the organic fertilizer KoHeA + MF, various types of natural PGRs, and their interactions on thegermination and early vegetative growth of red chilli seeds of the Lotanbar variety. The experiment employed aCompletely Randomized Design (CRD) factorial arrangement with four doses of KoHeA + MF organic fertilizer (0, 5,10, and 15 tons/ha) and four types of natural PGRs (no PGR, young coconut water, shallot extract, and bambooshoot extract), each applied at a 50% concentration. The variables observed included germination rate, maximumgrowth potential, plant height, leaf length, and number of leaves. Results indicated that KoHeA + MF organicfertilizer significantly influenced vegetative growth of red chilli plants, whereas natural PGRs enhanced seedgermination rates. The optimal treatment combined a planting medium mixed with KoHeA + MF at 10 tons/ha andseed soaking in natural PGR derived from young coconut water